If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2y + -8) + -4 = -4(y + -2) Reorder the terms: -5(-8 + 2y) + -4 = -4(y + -2) (-8 * -5 + 2y * -5) + -4 = -4(y + -2) (40 + -10y) + -4 = -4(y + -2) Reorder the terms: 40 + -4 + -10y = -4(y + -2) Combine like terms: 40 + -4 = 36 36 + -10y = -4(y + -2) Reorder the terms: 36 + -10y = -4(-2 + y) 36 + -10y = (-2 * -4 + y * -4) 36 + -10y = (8 + -4y) Solving 36 + -10y = 8 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 36 + -10y + 4y = 8 + -4y + 4y Combine like terms: -10y + 4y = -6y 36 + -6y = 8 + -4y + 4y Combine like terms: -4y + 4y = 0 36 + -6y = 8 + 0 36 + -6y = 8 Add '-36' to each side of the equation. 36 + -36 + -6y = 8 + -36 Combine like terms: 36 + -36 = 0 0 + -6y = 8 + -36 -6y = 8 + -36 Combine like terms: 8 + -36 = -28 -6y = -28 Divide each side by '-6'. y = 4.666666667 Simplifying y = 4.666666667
| (5-0)+6=5+6 | | -2y+5=-6y | | 1+p/-2=6 | | 0.12x+0.10(1500-x)=1600 | | 3x-4y=60 | | |5-(3)*4|*(-2)*-3*(-4)= | | -165x^3+198x= | | 7(p+2)=49 | | -6w+5/2=-3/2w-4/3 | | 6.7=52x+12.3 | | 4-3(x+2)=5(x-2) | | -3x-45=-8x | | X-2+3x=17 | | -5=4x-7-6 | | -7=6-29 | | 0=625000-259000/7t | | (3x+1)+(7x+4)=90 | | a-2+8=14 | | 25x^2-90=0 | | 20=7x+2-5x | | -8x-47=-x-5 | | (-3b)(13b-5)= | | 0=8b-b | | [(11x)(10x+11)]-[(16x+14)-(10x+16)]= | | 2m+3=-3 | | 220+0.92=428.84 | | c^3=c^3 | | -3(2x+9)=-6x+27 | | |5-(3)4|(-2)-3(-4)= | | 13cd^3+39c^2d^2=0 | | 8/(4c^2+16) | | ln(x)+ln(9x)=7 |